Damages for breach of contract, impossibility of performance and legal enforceability - Germán Coloma (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2007)
This paper develops a game-theoretic model of a contract between a creditor and a debtor where equilibrium depends on the damage rule chosen for breach-of-contract situations, the use of impossibility-of-performance excuses and the level of legal contract enforceability. We find that, under perfect legal enforceability, the different alternative damage rules (based on expectation or reliance damages, with or without performance excuses) are able to induce an efficient performance by the contracting parties. But we also find that, if legal enforceability is imperfect, then a rule based on expectation damages with an excuse for impossibility of performance is able to work more efficiently than the other alternative damage rules.
Keywords: K12; 330; breach of contact; impossibility of performance; legal enforceability